2020
DOI: 10.1055/a-1274-2959
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Difluoroalkylated Isoindolinones via Chiral Spirocyclic Phosphoric Acid Catalyzed Mannich-Type Reaction

Abstract: An enantioselective Mannich-type reaction of in situ generated cyclic ketimines with difluoroenoxysilanes catalyzed by chiral spirocyclic phosphoric acid has been developed. This methodology provides a facile route to difluoroalkyl-substituted chiral isoindolinones bearing a quaternary stereogenic center in high yields and up to 96% enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…3‐trifluoroalkylquinoxalin‐2(1 H )‐ones bearing various functional groups were formed via a radical pathway, which was basically consistent with that of Wei, Li group. Subsequently, Lin and coworkers [24] developed a H 2 O 2 ‐mediated hydrocarbylation reaction of quinoxaline‐2(1 H )‐ones and styrene, exhibiting good product yields (26 examples, 43 %‐84 % yields) and good functional group tolerance (alkyl, aryl, halogen, etc .) (Scheme 7).…”
Section: Carbon‐centered Radical Speciesmentioning
confidence: 99%
“…3‐trifluoroalkylquinoxalin‐2(1 H )‐ones bearing various functional groups were formed via a radical pathway, which was basically consistent with that of Wei, Li group. Subsequently, Lin and coworkers [24] developed a H 2 O 2 ‐mediated hydrocarbylation reaction of quinoxaline‐2(1 H )‐ones and styrene, exhibiting good product yields (26 examples, 43 %‐84 % yields) and good functional group tolerance (alkyl, aryl, halogen, etc .) (Scheme 7).…”
Section: Carbon‐centered Radical Speciesmentioning
confidence: 99%
“…Isoindolinones represent an important class of biologically active small molecules and have seen increasing applications in medicinal chemistry. 1,2 It has been reported that isoindolinones exhibit widespread biological activity, 2 including antitumor, anti-inflammatory, antiviral, and anti-addictive effects. Many synthetic pharmaceutical molecules contain isoindolinones, such as MDM2-p53 inhibitors, 3 PI3Kγ inhibitors, 4 RSV inhibitors, 5 HIV-1 reverse transcriptase inhibitors, 6 muscarinic acetylcholine receptor modulators 7 and anticancer agents 8 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%